Altitudinal changes in Rubisco and APX activities in Aconogonum weyrichii in the alpine region of Mt. Fuji - Sakata, Tsuyoshi; Nakano, Takashi; Yokoi, Yota (National Institute of Polar Research, 2006)
P(論文) o identify the determinants of the altitudinal distribution of an alpine herbaceous plant (Aconogonum weyrichii) from an eco-physiological viewpoint, we investigated the leaf characteristics concerned with photosynthetic capacity and tolerance of oxidative stress throughout this species altitude distribution on Mt. Fuji. Larger amounts of leaf nitrogen and Rubisco were found in populations growing at higher altitudes; however, initial activity of Rubisco did not increase with altitude in the summer, indicating that inactivation of Rubisco occurred in the higher populations. This inactivation would lead to a decrease in photosynthetic nitrogen use efficiency. When the leaves of A. weyrichii began to turn yellow in autumn, amounts of leaf nitrogen and Rubisco remarkably decreased in all populations throughout the altitude distribution. However, Rubisco activity in the higher populations did not decline until immediately before defoliation, suggesting that recovery from Rubisco inactivation occurred in these populations. The higher populations had a higher activity of APX than lower populations, contributing to maintaining Rubisco activity and photosynthetic production until the end of the growing period, which, in turn, are necessary for survival at higher altitudes. departmental bulletin paper